Cover Image. Issue 4 (1st November 2019) - Unknown
Abstract : Caption (upper right): Nunavik ship docking at Deception Bay port, Nunavik (northern Quebec). Credit: Antoine Dispas Caption (Upper left): Collecting water samples for eDNA between cracks in the ice at high tide near Iqaluit, Nunavut – In the photo: Anaïs Lacoursière and Kimberley Howland Credit: Dustin Raab Caption (bottom right): Ocean nearby Iqaluit, Nunavut. Credit: Anaïs Lacoursière Caption (bottom left): Deploying a benthic trawl for collection of specimen‐based samples to compare with paired eDNA water samples in Deception Bay, Nunavik (northern Quebec). Credit: Kimberly Howland